The Antimalarial Properties Of Essential Oils Of The Leaves Of Malaysian Plectranthus Amboinicus (Lour) Spreng In Mice Infected With Plasmodium Berghei - R., Norazsida; O., Pakeer; M., Taher (IIUM Medical Journal Malaysia, 2017)
This study was conducted to evaluate the phytochemical contents and antimalarial properties of the oils extracted from the leaves of Malaysian Plectranthus amboinicus in mice infected with Plasmodium berghei. The essential oils were extracted and prepared by using steam distillation technique and subjected to phytochemical screening by using GC-MS. Antimalarial activity of different extract doses of the essential oil was tested in vivo in ICR mice infected with Plasmodium berghei (PZZ1/100) during early, established and residual infections. In all, 5 compounds made up 88.34% of total oil and the major chemical compounds were carvacrol (85.14%), thymoquinone (1.65%), terpinen-4-ol (0.70%), octenol (0.62%) and thymol (0.23%). Antimalarial assay showed this essential oil as a potential prophylactic agent with the percentage chemosuppression of 45.23%, 18.28%, 45.38% and 58.26% while treated with 50, 200, 400 and 1000 µL/kg respectively of essential oil and curative agent with percentage of chemo suppression of 54.10%, 47.35%, 56.75% and 65.38% while treated with the above dose of essential oil. Statistically no reduction of parasitemia was calculated for suppressive test. The extract has prophylactic and curative effects on P.berghei in mice.